Pemodelan Motivasi Turis ke dalam Model Matriks Fuzzy untuk Pengembangan Pariwisata Masa Depan Berkelanjutan (Studi Kasus Agrowisata Paloh Naga) - Indah, Nurliyah; Sitompul, Pardomuan (Journal of Mathematics Education and Science, 2025)
Paloh Naga Agrotourism is a popular destination for domestic and foreign tourists. Data from the Village-Owned Enterprises (BUMDes) shows a decrease in the number of visits during the period 2021 to 2024. This study aims to apply a fuzzy matrix model with the CETD (Combined Effective Time Dependent Data) method in analyzing tourist motivation and identifying the most significant motivational factors based on age group. The analysis results show that intellectual factors are dominant in the 15-17 age group. Social factors have a strong influence on the 26-30 age group, at the age of 18-25 the influence of social factors decreases and continues to decline in the 36-60 age group. Competence factors have an influence at the age of 15-17 and lose their influence at the age of 18-30 years. The relaxation factor had a significant influence on the 15-17 age group, especially for the need to escape from daily activities, and for the 26-30 age group the relaxation factor was irrelevant. These insights provide valuable implications that tourism managers tailor to the needs of each age group. Future research could extend the analysis with other demographic variables or advanced quantitative approaches.